Multidrug Resistance Reversal Effects of Aminated Thioxanthones and Interaction with Cytochrome P450 3A4 - Andreia Palmeira; Maria Emília Sousa; Miguel X Fernandes; Madalena M. Pinto; M. Helena Vasconcelos (Frontiers Media S.A., 2011)
Purpose. Aminated thioxanthones have recently been described as dual-acting agents: growth inhibitors of leukemia cell lines and P-glycoprotein (P-gp) inhibitors. To evaluate the selectivity profile of thioxanthones as inhibitors of multidrug resistance (MDR), their interaction with other ABC transporters, which were found to have a strong correlation with multidrug resistance, such as multidrug resistant proteins 1 (MRP1), 2 (MRP2) and 3 (MRP3) and breast cancer resistance protein (BCRP) was also evaluated. The interaction of thioxanthones with cytochrome P450 3A4 (CYP3A4) together with the prediction of their binding conformations and metabolism sites was also investigated. Methods. The UIC2 monoclonal antibody-labelling assay was performed using P-gp overexpressing leukemia cells, K562Dox, incubated with eight thioxanthonic derivatives, in order to confirm their P-gp inhibitory activity. A colorimetric-based ATPase assay using membrane vesicles from mammalian cells overexpressing a selected human ABC transporter protein (P-gp, MRP1, MRP2, MRP3, or BCRP) was performed. To verify if some of the thioxanthonic derivatives were substrates or inhibitors of CYP3A4, a luciferin-based luminescence assay was performed. Finally, the in silico prediction of the most probable metabolism sites and docking studies of thioxanthones on CYP3A4 binding site were investigated. Results. Thioxanthones interacted not only with P-gp but also with MRP and BCRP transporters. These compounds also interfere with CYP3A4 activity in vitro, in accordance with the in silico prediction. Conclusion. Thioxanthonic derivatives are multi-target compounds. A better characterization of the interactions of these compounds with classical resistance mechanisms may possibly identify improved treatment applications. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.